Effect of freshwater mussels on the vertical distribution of anaerobic ammonia oxidizers and other nitrogen-transforming microorganisms in upper Mississippi river sediment - Black, Ellen M. (PeerJ, 2017)
Targeted qPCR and non-targeted amplicon sequencing of 16S rRNA genes within sediment layers identified the anaerobic ammonium oxidation (anammox) niche and characterized microbial community changes attributable to freshwater mussels. Anammox bacteria were normally distributed (Shapiro-Wilk normality test, W-statistic =0.954, p = 0.773) between 1 and 15 cm depth and were increased by a factor of 2.2 (p < 0.001) at 3 cm below the water-sediment interface when mussels were present. Amplicon sequencing of sediment at depths relevant to mussel burrowing (3 and 5 cm) showed that mussel presence reduced observed species richness (p = 0.005), Chao1 diversity (p = 0.005), and Shannon diversity (p < 0.001), with more pronounced decreases at 5 cm depth. A non-metric, multidimensional scaling model showed that intersample microbial species diversity varied as a function of mussel presence, indicating that sediment below mussels harbored distinct microbial communities. Mussel presence corresponded with a 4-fold decrease in a majority of operational taxonomic units (OTUs) classified in the phyla Gemmatimonadetes, Actinobacteria, Acidobacteria, Plantomycetes, Chloroflexi, Firmicutes, Crenarcheota, and Verrucomicrobia. 38 OTUs in the phylum Nitrospirae were differentially abundant (p < 0.001) with mussels, resulting in an overall increase from 25% to 35%. Nitrogen (N)-cycle OTUs significantly impacted by mussels belonged to anammmox genus Candidatus Brocadia, ammonium oxidizing bacteria family Nitrosomonadaceae, ammonium oxidizing archaea genus Candidatus Nitrososphaera, nitrite oxidizing bacteria in genus Nitrospira, and nitrate- and nitrite-dependent anaerobic methane oxidizing organisms in the archaeal family “ANME-2d” and bacterial phylum “NC10”, respectively. Nitrosomonadaceae (0.9-fold (p < 0.001)) increased with mussels, while NC10 (2.1-fold (p < 0.001)), ANME-2d (1.8-fold (p < 0.001)), and Candidatus Nitrososphaera (1.5-fold (p < 0.001)) decreased with mussels. Co-occurrence of 2-fold increases in Candidatus Brocadia and Nitrospira in shallow sediments suggests that mussels may enhance microbial niches at the interface of oxic–anoxic conditions, presumably through biodeposition and burrowing. Furthermore, it is likely that the niches of Candidatus Nitrososphaera and nitrite- and nitrate-dependent anaerobic methane oxidizers were suppressed by mussel biodeposition and sediment aeration, as these phylotypes require low ammonium concentrations and anoxic conditions, respectively. As far as we know, this is the first study to characterize freshwater mussel impacts on microbial diversity and the vertical distribution of N-cycle microorganisms in upper Mississippi river sediment. These findings advance our understanding of ecosystem services provided by mussels and their impact on aquatic biogeochemical N-cycling.